Analysis of Taxpayer's Compliance Level in Paying Rural Urban Land and Building Taxes (PBB-P2) in the Regional Revenue Agency of Padang City - Herfina, Melli (Dinasti Publisher, 2021)
This study aims to determine the level of taxpayer compliance for the Rural and Urban Land and Building Tax (PBB-P2) to local regulations and laws that apply in the city of Padang, discipline, responsibility, level of self-awareness of taxpayers. know the efforts to what affects the level of compliance as well as land and building tax receipts. The research on the level of taxpayer compliance in paying land and building taxes at the Padang City Regional Revenue Agency is a shared learning so that they can participate in providing support in development, increase self-awareness and participate in providing support for local government administration. The system applied in PBB-P2 tax is the Official Assessment system, namely a tax collection system that imposes the authority to determine the amount of tax owed to the tax authorities or tax officials as tax collectors. Sanctions imposed on taxpayers if they do not pay taxes are administrative sanctions in the form of a fine of 2% per month, an interest penalty of 2% every month and an increase of 25%. Legal Basis for Land and Building Tax in Rural Urban (PBB-P2), namely, Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. The level of taxpayer compliance in paying PBB-P2 taxes in the city of Padang seen from its realization is still relatively low, every year from 2017 to 2020 it has not exceeded the set target.